Comprehensive literature review of oral and intravenous contrast-enhanced PET/CT: a step forward? - Metrard, Gilles; Cohen, Clara; Bailly, Matthieu (Frontiers in Medicine, 2024)
The integration of diagnostic CT scans into PET/CT facilitates a comprehensive single examination, presenting potential advantages for patients seeking a thorough one-shot check-up. The introduction of iodinated contrast media during PET scanning raises theoretical concerns about potential interference with uptake quantification, due to the modification of tissue density on CT. Nevertheless, this impact appears generally insignificant for clinical use, compared to the intrinsic variability of standardized uptake values. On the other hand, with the growing indications of PET, especially 18F-FDG PET, contrast enhancement increases the diagnostic performances of the exam, and provides additional information. This improvement in performance achieved through contrast-enhanced PET/CT must be carefully evaluated considering the associated risks and side-effects stemming from the administration of iodinated contrast media. Within this article, we present a comprehensive literature review of contrast enhanced PET/CT, examining the potential impact of iodinated contrast media on quantification, additional side-effects and the pivotal clinically demonstrated benefits of an all-encompassing examination for patients. In conclusion, the clinical benefits of iodinated contrast media are mainly validated by the large diffusion in PET protocols. Contrary to positive oral contrast, which does not appear to offer any major advantage in patient management, intravenous iodine contrast media provides clinical benefits without significant artifact on images or quantification. However, studies on the benefit–risk balance for patients are still lacking.